PHILOSOPHICAL LYRIC POETRY AS SPECIAL FORM OF REFERENT POETRY - Derkachova , O. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the features of philosophical lyric poetry are considered in the context of referent lyric. Principles of image of the world are analyzed in philosophical referent poetry. Its features in the conditions of «block» are determined.